Adverse Oral Health and Cognitive Decline: The Health, Aging and Body Composition Study. Issue 2 (13th February 2013) - Stewart, Robert; Weyant, Robert J.; Garcia, Melissa E.; Harris, Tamara; Launer, Lenore J.; Satterfield, Suzanne; Simonsick, Eleanor M.; Yaffe, Kristine; Newman, Anne B.
<x xml:space="preserve">Abstract</x> Objectives To investigate the relationship between periodontal disease and cognitive decline. Design Analysis of a prospective cohort study. Setting The Health, Aging and Body Composition (Health ABC) Study. Participants One thousand fifty‐three participants who were administered the Modified Mini‐Mental State Examination (3MS) at Year 1 (baseline) and Year 3 and had participated in a comprehensive periodontal examination at Year 2. Measurements The prospective association between a range of oral health parameters and cognitive function was examined. Decline in 3MS score from Year 3 to 5 was investigated in 947 (89.9%) participants. Covariates included age, sex, education, race, cardiovascular disease and risk, and depressive symptoms. Results Most indicators of adverse oral health at Year 2 were associated with cognitive impairment based on averaged 3MS scores less than 80 for Years 1 and 3, but education and race substantially confounded these associations. Higher gingival index, a measure of gingival inflammation, at Year 2 remained independently associated with this definition of cognitive impairment and, in fully adjusted analyses, was also an independent predictor of a more‐than‐5‐point cognitive decline from Year 3 to 5. Conclusion Periodontitis may be a risk factor for cognitive decline. Gingivitis is reversible, and periodontitis to some degree is preventable and controllable when manifest. Therefore, further research is needed to clarify potential underlying mechanisms and oral health interventions that might ameliorate cognitive decline.